PHYSICAL QUALITY AND INVITRO SILASE OF RICE PINE PEOPLE DISUPLEMENTED BY GAMAL AND KALIANDRA LEAVES - I G. B., Basudewa; Cakra, I G. L. O.; Siti, N. W. (Jurnal Peternakan Tropika, 2020)
This study aims to determine the physical quality and digestibility of in vitro silage of rice straw supplemented with gamal and kaliandra leaves. The study used a Completely Randomized Design (CRD), consisting of four treatments and each treatment was repeated five times, so that there were 20 experimental units. The treatments given were: P0 (90% rice straw + 5% molasses + 5% polar), P1 (60% rice straw + 30% gamal leaf + 5% molasses + 5% polar), P2 (60% rice straw + 15 % gamal leaves + 15% calliandra leaves + 5% molasses + 5% polar) and P3 (60% rice straw + 30% calliandra leaves + 5% molasses + 5% polar). The observed variables were pH, NH 3 , VFA (Vollatile Faty cid), DMD (Dry  Matter Digesribility), OMD (Organic Matter Digestibility), fungus, texture, color, and odor. The resul showed that the concentration of NH 3 in the P1 treatment was higher than the P0, P2 and P3 treatments respectively 36.88%, 33.76% and 38.92%. Total pH and VFA values ??did not show significant differences between all treatments. DMD and OMD in P1 treatment were higher than P0, P1 and P2 treatments. It can be concluded that making rice straw silage with the addition of 30% gamal can improve silage quality both in terms of NH 3 and organoleptic testing, namely color and texture. DMD and OMD are highest in P1 because gamal contains a degraded source of protein (protein needed by rumen microbes) that is more comparable to calliandra.   Keywords : Rice straw silage, physical quality, digestibility